Mothers' Care-Seeking Behavior for Common Childhood Illnesses and Its Predictors in Ethiopia: Meta-Analysis. (18th October 2022) - Tekalign, Tiwabwork; Guta, Mistire Teshome; Awoke, Nefsu; Asres, Abiyot Wolie; Obsa, Mohammed Suleiman
Abstract : Background. Healthcare-seeking interventions can potentially reduce child mortality; however, many children die in developing countries without reaching a health facility. The World Health Organization reported that 70% of child deaths are related to delay care-seeking. So, this review is aimed at identifying mothers' care-seeking behavior for common childhood illnesses and predictors in Ethiopia. Methods. Systematic search of studies was done on PubMed, Scopus, Web of Science, institutional repositories, Academic Search Premier, and manually from reference lists of identified studies in the English language up to August 2021. The quality of the studies was evaluated by the Joanna Briggs Institute (JBI) quality appraisal tool for prevalence study. This meta-analysis used the random-effect method using the STATA™ Version 14 software. Result. Fourteen studies involving 8, 031 participants were included in this meta-analysis. After correcting Duval and Tweedie's trim and fill analysis, the overall pooled prevalence of mothers' care-seeking behavior is 60.73% (95% CI: 43.49-77.97), whereas the highest prevalence, 74.80% (95% CI: 62.60, 87.00) and 67.77%(95% CI: 55.66, 79.87), was seen in Amhara region and urban residents, respectively, while the lowest, 36.49% (95% CI: -27.21, 100.18) and 47.80% (95% CI:-15.31, 110.9), was seen in South Nation Nationality Peoples' Regions and among rural residents, respectively. Mothers' educational status (P ≤ 0.001 ) and mothers' marital status (P ≤ 0.001 ) were significantly associated with mothers' care-seeking behavior. Conclusion. Even though children are a vulnerable group, mothers' care-seeking behavior for common childhood illnesses is significantly low. Educational status and marital status were determinants of mothers' care-seeking behavior. So, all responsible bodies should work on the improvement of mothers' care-seeking behavior.